3-D atom probe studies of some nanostructured materials - Warren, P; Thuvander, M; Abraham, M; Lane, H; Cerezo, A; Smith, G (2000)
This paper reports recent results of our 3-dimensional atom probe (3DAP) investigations of two different examples of nanostructured materials; electrodeposited nanocrystalline Ni and NI-P alloys and melt-spun amorphous nanocrystalline Fe-Si-Cu-Nb-B-Al alloys.3DAP analysis of as-deposited nanocrystalline Ni showed a uniform distribution of about 0.1at.% of impurity atoms, most of which were sulphur. Such low impurity levels and lack of grain boundary pinning enables grain growth to occur during heating at only 200 degrees C. In the Ni-P alloys, however, 3DAP showed clear evidence of P segregation and formation of Ni3P particles during heat treatment at 425 degrees C. As a result, nanocrystalline Ni-P alloys are found to be significantly stabilized relative to nanocrystalline pure Ni alloys.3DAP analysis of nanocrystalline Fe71.5Si13.6Cu1Nb3B9Al2 showed that the Al strongly partitions away from the amorphous matrix into the nanocrystals, also then was strong partitioning of the Al into the Cu-rich particles and corresponding depletion of Al in the amorphous matrix. The partitioning of the Al to the Fe-Si nanocrystals is thought to be the cause of the reduced coercivity and magnetostriction and magnetic anisotropy in this alloy.